2008
DOI: 10.1177/0269881108092337
|View full text |Cite
|
Sign up to set email alerts
|

Is there a neuroendocrinological rationale for testosterone as a therapeutic option in depression?

Abstract: Depression is a disease of growing incidence and economic burden worldwide. In view of increasing treatment resistance, new therapeutic approaches are urgently needed. In addition to its gonadal functions, testosterone has many effects on the central nervous system. An association between testosterone levels and depressive symptoms has been proposed. Many hormones and neurotransmitters are involved in the aetiology and the course of depression including serotonin, dopamine, noradrenaline, vasopressin and corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 180 publications
(194 reference statements)
0
36
0
1
Order By: Relevance
“…Nevertheless, most studies do not show any association between T plasma levels and depression [85,89]. It has been suggested that low T is related to mild dysthymic symptoms rather than major depression [85].…”
Section: Mood Disordersmentioning
confidence: 98%
See 4 more Smart Citations
“…Nevertheless, most studies do not show any association between T plasma levels and depression [85,89]. It has been suggested that low T is related to mild dysthymic symptoms rather than major depression [85].…”
Section: Mood Disordersmentioning
confidence: 98%
“…T easily crosses the blood-brain barrier. It is also a neurosteroid synthesized in the central nervous system (CNS) [85]. Androgen and GnRH receptors are present in several CNS structures related to depression [57,58,82,85,86].…”
Section: Mood Disordersmentioning
confidence: 99%
See 3 more Smart Citations